Harnessing the Anti-Inflammatory Potential of Lamiaceae Family Hydrolates: A Study of Satureja Montana and Origanum Vulgare in Burn Wound Management - Parshenkov, Mikhail; Tokov, Alibek; Kuzminov, Boris; Sataieva, Tatiana; Popov, Sergey; Tarasov, Vadim; Tuktarova, Amira; Demyashkin, Grigory (Scripta Medica, 2025)
Background/Aim: The management of severe thermal injuries is a significant clinical challenge, often leading to protracted inflammation, impaired tissue regeneration and increased susceptibility to infection, a situation exacerbated by growing antimicrobial resistance. Existing treatments frequently offer limited efficacy, creating a demand for novel treatment modalities. Our investigation explores the therapeutic efficacy of innovative hydrogels formulated with hydrolates from two Lamiaceae family species, Satureja montana L and Origanum vulgare L, to modulate recovery after skin burn. Methods: Standardised grade IIIa thermal burns were induced in twenty-five rabbits. The animals were then randomised into several cohorts for treatment: groups receiving topical applications of either Satureja montana L hydrolate gel, Origanum vulgare L hydrolate gel, or a standard therapeutic regimen. Control groups consisted of animals with untreated burns and healthy controls. To assess systemic inflammation, serum concentrations of key pro-inflammatory markers, interleukin-6, tumour necrosis factor-alpha and C-reactive protein, were quantified in serum via ELISA, while plasma levels of oxidative stress indicators (malondialdehyde (MDA), superoxide dismutase (SOD), reduced glutathione (GSH)) were determined via specific colorimetric assay kits. Histopathological analysis (HE staining) assessed tissue regeneration and inflammation and IL-1β immunohistochemistry evaluated inflammatory. Results: After fourteenth days post-injury, the cohort treated with Satureja montana L hydrolate exhibited a reduction in systemic inflammatory markers, approaching physiological baseline levels. Histological examination confirmed epithelialisation, markedly reduced inflammatory cell infiltration and robust inflammation reduction in this group. While Origanum vulgare L also showed beneficial effects, Satureja montana L consistently outperformed both its herbal counterpart and conventional treatments in promoting tissue repair and immunomodulation. Conclusion: Presented findings indicate that phytotherapeutic preparations utilising hydrolates, especially the formulation derived from Satureja montana L, constitute a highly promising adjunctive strategy for the clinical management of thermal burn injuries.